Comparison between conventional and micro-assisted periodontal surgery: Case series - Chanchal Katariya; Arvina Rajasekar (Wolters Kluwer Medknow Publications, 2022)
Microsurgery is a minimally invasive procedure that uses a surgical microscope, specially designed equipment, and suture materials. Even though this equipment and expertise of numerous surgeries are required to meet patient esthetic reckoning, doctors must be ready to invest time and effort into becoming familiar with novel surgical methods and devices. The ambition of this case series is to compare conventional macro surgery and microsurgery in terms of clinical approach. This study included four cases, two flap surgery, and two root coverage. Clinical parameters for root coverage, increase in keratinized tissue (KT), gain in clinical attachment level (CAL) and complete root coverage (CRC), dentin hypersensitivity index-Schiff's index and for flap surgery, probing depth, clinical attachment level. Healing and pain analysis were done. There was no significant difference seen between conventional and clinical outcomes of a microsurgical technique such as clinical attachment level, probing depth, increase in KT, gain in clinical attachment level (CAG), and CRC, dentin hypersensitivity index-Schiff's index. When patient-based outcomes such as healing index and Visual Analog Scale, a significant difference was seen. If a microsurgical method is used instead of a traditional macroscopic approach, the early healing index can be significantly improved and there will be less postoperative pain.